The international politics of the Middle East - Hinnebusch, Raymond A. (Regional international politics series., 2003)
This text aims to fill a gap in the field of middle eastern political studies by combining international relations theory with concrete case studies. It should be of benefit to students of middle eastern politics, international relations and comparative politics.